2022
DOI: 10.23910/1.2022.2715
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Haulm Cutting, Size of Seed Tubers/Seed Pieces and Intra-Row Spacings on Tuber Yield and Economics of Potato Production

Abstract: The field experiments were conducted during two consecutive rabi seasons (October – February) during 2019–20 and 2020–21 at ICAR-Central Potato Research Institute Regional Station, Gwalior, Madhya Pradesh, India located in west central plains of India. Highest emergence of potato plants was recorded with the planting of 40 g whole tubers. Growth attributes viz. plant height (58.6 cm) and number of compound leaves (56.7) were recorded highest with 40 g seed piece/whole tuber. Planting of 120 g seed tubers, 10 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…By the way, several studies (eg. Thakral et al, 1989;Manorama, 2004; Singh et al, 2018) [28,18,26] confirmed that the most critical period for weed removal in potatoes is about 4 to 6 weeks after planting. [3,14] reported that potato growers usually apply herbicide early postemergence.…”
Section: Figmentioning
confidence: 98%
See 2 more Smart Citations
“…By the way, several studies (eg. Thakral et al, 1989;Manorama, 2004; Singh et al, 2018) [28,18,26] confirmed that the most critical period for weed removal in potatoes is about 4 to 6 weeks after planting. [3,14] reported that potato growers usually apply herbicide early postemergence.…”
Section: Figmentioning
confidence: 98%
“…This density variation in the different studied plots was probably due to differences in applied agrotechnical practices. In fact, the occurrence and intensity of weeds vary under various agroclimatic regions, cropping systems and management conditions (Singh et al, 2018) [26] . High weed density was confirmed by the species biomass variation (Fig 2).…”
Section: Effects Of Chemical and Hand Weeding Practices On Weed Flora...mentioning
confidence: 99%
See 1 more Smart Citation
“…Size of seed tuber is an important factor to decide the seed per unit area because it affects total yield and graded or marketable tuber yields Kushwah, 2010 andDagne et al, 2019). The approximate intra-row spacing for <25, 25-60, 60-100 and >100 g seed size tubers is 15, 20, 25 and 30 cm with inter-row spacing of 60 cm, respectively is suggested under SPT (Sharma et al, 2021).…”
Section: Seed Tuber Sizementioning
confidence: 99%
“…If larger seed is used, a greater quantity of seed is required for planting per unit area. It is avoided because it increases seed costs and reduce planter's accuracy (Singh and Kushwah, 2010). Conversely, smaller seed size tubers have less sprouts per unit due to the lesser amount of reserves available for sprout growth leading to small number of stems that produce only a few tubers, thereby reducing yield (Dagne, 2015).…”
Section: Introductionmentioning
confidence: 99%